Radiotherapy in Fibrodysplasia Ossificans Progressiva: A Case Report and Systematic Review of the Literature - Botman, Esmée; Netelenbos, Jan Coen; Rustemeyer, Thomas; Schoonmade, Linda J.; Nieuwenhuijzen, Jakko A.; Teunissen, Bernd P.; Visser, Marieke; Raijmakers, Pieter; Lammertsma, Adriaan A.; Dahele, Max; Eekhoff, Marelise (Frontiers in Endocrinology, 2020)
Fibrodysplasia Ossificans Progressiva (FOP) is an autosomal dominant disease, characterized by the formation of heterotopic ossification (HO) in muscles, ligaments and tendons. Flare-ups, an inflammatory process that often precedes the formation of HO, can occur spontaneously, but trauma is also a common trigger. It is not known whether radiotherapy, especially in higher doses, might cause sufficient trauma or inflammation to trigger a flare-up and subsequent HO in FOP patients. We report the case of a patient undergoing radiotherapy for the treatment of a 1 centimetre wide basal cell carcinoma (BCC) of the lower lip. In addition, we present a systematic review of the available literature. Our patient received 54 Gy in 18 fractions with orthovoltage therapy, resulting in a clinical complete response of the tumour. Six months after treatment, there were no signs of HO either clinically or on [18F]NaF PET/CT. The systematic review identified eleven publications describing either radiation treatment in FOP or radiation therapy as a cause of HO in non-FOP patients. Six case reports described the use of radiation in FOP patients for various reasons, including one with a high dose treatment of a lip BCC using superficial X-ray therapy. The remaining five studies described the use of low dose radiotherapy to prevent or treat either a FOP flare-up or HO formation. None of these cases showed worsening of disease that could be attributed to the use of radiation therapy. Radiation induced HO in non-FOP patients was rare and occurred in five studies. The largest of these studies suggested that HO was induced after treatment with high doses, resulting in more widespread evidence of tissue damage, potentially being the end result of this damage. In conclusion, available reports suggest no contraindication to radiotherapy in FOP patients, although the number of cases was small, systematic toxicity reports often were not available and none of the reports described high dose, high energy radiation treatment at locations such as muscle and joint regions.